In vitro bioaccessibility of calcium, iron and zinc from breads and bread spreads - Ting, S. R.; Loh, Su Peng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The in vitro bioaccessibility of calcium, iron and zinc of breads added with different bread spreads was determined. The mineral contents were assessed by flame atomic absorption spectrophotometer and expressed in fresh weight (mg/100 g). For the mineral bioaccessibility determination, in vitro gastrointestinal digestion was applied. Among the bread samples, calcium content of wholemeal bread with chocolate hazelnut spread ranked the highest (159.96±0.869 mg/100 g). For iron, white bread with chocolate hazelnut spread (6.92±0.411 mg/100 g) showed highest iron content while for zinc, white bread with peanut butter was the highest (1.82±0.015 mg/100 g). For calcium bioaccessibility, white bread with orange marmalade ranked the highest (39.33±4.865%) while wholemeal bread with peanut butter (14.70±0.265%) showed the lowest. The application of orange marmalade spread onto wholemeal bread increased the iron bioaccessibility significantly (9.73±1.387%). The acidic properties attributed by organic acids found in orange marmalade may favour both calcium and iron absorption. The zinc bioaccessibility of white bread alone remained the highest (20.63±3.536%) while wholemeal bread added with peanut butter (5.90±1.137%) showed the lowest. Overall, the addition of bread spreads particularly peanut butter and chocolate hazelnut spread had increased mineral contents of the bread samples. However, the presence of mineral enhancers (organic acids) and inhibitors (phytate and polyphenols) played some significant role in influencing the mineral bioaccessibility.